Group Exhibition-Is this the Time for Art? Migration, Politics of Borders and Art. - Antoniou, Klitsa (My University, 2026)
Is this the Time for Art? Migration, Politics of Borders and Art. The Museum of Forgetting, Norrköping, Sweden. Curated by Erik Berggren with input from Kosta Economou. With support by The Swedish Arts Council, Region Östergötland and Fastighets AB L E Lundberg.